The limited effects of partisan and consensus messaging in correcting science misperceptions. (May 2021) - Chockalingam, Vignesh; Wu, Victor; Berlinski, Nicolas; Chandra, Zoe; Hu, Amy; Jones, Erik; Kramer, Justin; Li, Xiaoqiu Steven; Monfre, Thomas; Ng, Yong Sheng; Sach, Madeleine; Smith-Lopez, Maria; et al.
The spread of COVID-19 misinformation highlights the need to correct misperceptions about health and science. Research on climate change suggests that informing people about a scientific consensus can reduce misinformation endorsement, but these studies often fail to isolate the effects of consensus messaging and may not translate to other issues. We therefore conduct a survey experiment comparing standard corrections with those citing a scientific consensus for three issues: COVID-19 threat, climate change threat, and vaccine efficacy. We find that consensus corrections are never more effective than standard corrections at countering misperceptions and generally fail to reduce them with only one exception. We also find that consensus corrections endorsed by co-partisans do not reduce misperceptions relative to standard corrections, while those endorsed by opposition partisans are viewed as less credible and can potentially even provoke a backfire effect. These results indicate that corrections citing a scientific consensus, including corrective messages from partisans, are less effective than previous research suggests when compared with appropriate baseline messages.